Online market research panel members as controls in case–control studies to investigate gastrointestinal disease outbreaks: early experiences and lessons learnt from the UK. Issue 4 (15th January 2018) - Mook, P.; McCormick, J.; Kanagarajah, S.; Adak, G. K.; Cleary, P.; Elson, R.; Gobin, M.; Hawker, J.; Inns, T.; Sinclair, C.; Trienekens, S. C. M; Vivancos, R.; et al.
Abstract: Established methods of recruiting population controls for case–control studies to investigate gastrointestinal disease outbreaks can be time consuming, resulting in delays in identifying the source or vehicle of infection. After an initial evaluation of using online market research panel members as controls in a case–control study to investigate a Salmonella outbreak in 2013, this method was applied in four further studies in the UK between 2014 and 2016. We used data from all five studies and interviews with members of each outbreak control team and market research panel provider to review operational issues, evaluate risk of bias in this approach and consider methods to reduce confounding and bias. The investigators of each outbreak reported likely time and cost savings from using market research controls. There were systematic differences between case and control groups in some studies but no evidence that conclusions on the likely source or vehicle of infection were incorrect. Potential selection biases introduced by using this sampling frame and the low response rate are unclear. Methods that might reduce confounding and some bias should be balanced with concerns for overmatching. Further evaluation of this approach using comparisons with traditional methods and population-based exposure survey data is recommended.